Puccini's La Bohème - Puccini, Giacomo, 1858-1924 (Opera classics library., 2001)
-- Engaging Commentary and Analysis about the composer, the opera and its characters.-- Story Narrative with Music Highlight Examples-- A complete Libretto (newly translated) that incorporates Music Highlight Examples-- A Discography-- A Videography-- A Dictionary of Opera and Musical TermsEach Opera Classics Library edition is a comprehensive guide and complete analysis and evaluation of a specific opera; each is a unique "encyclopedia" that integrates important and pertinent information about each timeless classic. The objective of Opera Classics Library is to unlock opera's mysteries for the general audience, and enlighten and educate. Understanding and knowledge are the master keys to enhance enjoyment and appreciation of this great art form. Puccini's La Boheme remains a treasured sentimental favorite of opera-goers worldwide. Certainly, the critic Harold Schoenberg had La Boheme in mind when he commented, "While the basis of Verdi's operas is a battle cry, the basis of Puccini's operas is a mating call." La Boheme is about youthful aspiration and tender love. Its poignant story and Puccini's soul-searching music emphasize how tragedy and grief can elevate humanity to consciousness, awareness, and maturity